2006
DOI: 10.1080/00220380500405634
|View full text |Cite
|
Sign up to set email alerts
|

Escaping poverty and becoming poor in 36 villages of Central and Western Uganda

Abstract: Twenty-four per cent of households in 36 village communities of Central and Western Uganda have escaped from poverty over the past 25 years, but another 15 per cent have simultaneously fallen into poverty. A roughly equal number of households escaped from poverty in the first period (ten to 25 years ago) as in the second period (the last ten years) examined here. However, almost twice as many households fell into poverty during the second period as in the first period. Progress in poverty reduction has slowed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 23 publications
2
38
0
Order By: Relevance
“…Adaptation (and coping) strategies do not automatically reduce household poverty, just like poverty reduction activities do not automatically improve capacity to respond to climatic stresses (Eriksen and O'Brien 2007). There are complex dynamics that exist in determining levels of poverty (see for example Okwi et al 2007;Krishna et al 2006). The literature provides valuable arguments concerning the need to consider both the direct impact of other stressors, and how coping with one stress can indirectly shape (2005) found, households prone to drought may relocate closer to water sources to cope with reduced water availability, yet in doing so increase their exposure and vulnerability to unexpected short term shocks such as flooding.…”
Section: Coping With Climate Induced Hazards In Rural Households In Umentioning
confidence: 99%
“…Adaptation (and coping) strategies do not automatically reduce household poverty, just like poverty reduction activities do not automatically improve capacity to respond to climatic stresses (Eriksen and O'Brien 2007). There are complex dynamics that exist in determining levels of poverty (see for example Okwi et al 2007;Krishna et al 2006). The literature provides valuable arguments concerning the need to consider both the direct impact of other stressors, and how coping with one stress can indirectly shape (2005) found, households prone to drought may relocate closer to water sources to cope with reduced water availability, yet in doing so increase their exposure and vulnerability to unexpected short term shocks such as flooding.…”
Section: Coping With Climate Induced Hazards In Rural Households In Umentioning
confidence: 99%
“…In Kenya, for example, a national survey revealed that of the sampled households that moved out of poverty between 1990 and 2005, half attributed their success to investment in agriculture (Kristjanson et al 2010). Similarly, 70 % of households that moved out of poverty in Uganda between 1980 and 2004 stated that the main driver of ascent was agriculture (Krishna et al 2006). This may seem to contradict our earlier results showing that income from new technology was not enough to lift a 2 ha farm above the poverty line.…”
Section: Discussionmentioning
confidence: 99%
“…poor over the whole period (Krishna, 2005). A study of developed countries found that 'In most European countries, the combination of modest inequality and extensive mobility among the poor enabled virtually all families to avoid relative deprivation at least occasionally' (Duncan, 1993, p.255).…”
Section: Horizontal and Vertical Inequality: A Clarificationmentioning
confidence: 99%